(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Data mining is one of the promising and continuously evolving fields in the arena of data analytics. Data mining has led to solutions of various unfathomable jobs, events, diseases and evaluations. The rich consortium of techniques that falls under the data mining domain makes it a formidable force for data scientists. The current paper reviews the various papers published on COVID-19 using data mining techniques to address the pandemic in terms of its explanation, assessment and solution. The current paper reviews the work done by various authors using data mining techniques. The paper contributes uniquely to the literature by filling up the gap of review on COVID-19 related work.